High-performance hollow fiber membrane and application thereof
Through wet spinning and post-treatment technology, a high-performance hollow fiber membrane was prepared, which solved the problem of mechanical performance degradation of existing membranes when increasing pore size, and achieved more effective removal of medium-molecular toxins and reduced costs.
Patent Information
- Application Number
- CN202411809793.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-02-28
AI Technical Summary
When the existing hollow fiber membranes increase the pore size to remove medium molecular toxins, their mechanical properties are degraded, their pore structure is uneven, and their cost is high.
The primary membrane of polyethersulfone/polysulfone hollow fiber membrane was prepared by wet spinning, and was post-treated at a relative humidity of 10-70%, 160-250°C to improve the crystallinity and pore size distribution of the membrane.
The mechanical properties and hemocompatibility of the hollow fiber membrane are improved, the pore size is increased to remove medium molecular toxins more effectively, while reducing costs.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention belongs to the field of organic membrane preparation, and specifically relates to a high-performance hollow fiber membrane and application thereof. Background Art
[0002] Blood purification refers to the process of removing certain pathogenic substances (toxins) from the patient's blood through a blood purification device to purify the blood and treat the disease. It includes a variety of treatment methods such as hemodialysis, hemoperfusion, and plasma exchange. Hemodialysis is the main treatment for patients with end-stage renal disease (ESKD), and hemodialysis membranes are the core components of hemodialysis treatment. The premise of hemoperfusion and plasma exchange is that plasma and blood cells need to be separated and processed through components or equipment. At present, hollow fiber membranes made of second-generation polymers such as polysulfone (PSf) and polyethersulfone (PES) have excellent thermal stability, chemical stability and mechanical stability. Polyethersulfone has high mechanical strength, stable chemical composition, good pressure resistance, heat resistance, aging resistance, corrosion resistance and other characteristics. It can be steam sterilized multiple times, is easy to reuse, and has a long service life. It has occupied a dominant position in hemodialyzer membranes and plasma separation membranes.
[0003] However, in order to maintain a good filtration rate and sufficient mechanical properties of the fiber membrane, the pore size of the current polysulfone / polyethersulfone hollow fiber membrane is relatively small, and it is mostly used to remove excess water and medium and small molecular weight uremic toxins in the blood. Hemodialysis membranes have limited removal effects on middle molecular toxins, such as parathyroid hormone, β2-microglobulin, interleukin, etc., and these middle molecular toxins are often closely related to complications such as inflammation, cardiovascular events, anemia and malnutrition in patients. Middle molecular toxins have a large molecular weight and are difficult to remove through conventional hemodialysis methods. It is necessary to further increase the pore size of the dialysis membrane, which places higher requirements on hollow fiber membranes.
[0004] As the pore size of the hollow fiber membrane increases, its mechanical properties are bound to decrease, and pore collapse is likely to occur at higher flow rates, and the quality of the fiber membrane cannot be guaranteed. Currently, only a few companies have the preparation technology for large-pore polyethersulfone / polysulfone fiber membranes, resulting in high costs for hollow fiber membranes. Therefore, providing a preparation method for hollow fiber membranes with simple process, high mechanical properties and large pore size is of great practical significance.
[0005] CN110404423A discloses a method for preparing a high-performance polyimide hollow fiber membrane, wherein the hollow fiber membrane is prepared by a dry-wet spinning process, and the mechanical strength and solvent resistance of the polyimide hollow fiber membrane are improved by a high-temperature annealing method. When the annealing temperature is close to the glass transition temperature, the annealing process can increase the tensile strength of the polyimide hollow fiber membrane, and when the annealing temperature is greater than the glass transition temperature, its tensile strength and solvent resistance can be significantly increased. This method is simple and effective, and has good application prospects in gas separation.
[0006] CN102228803A discloses a process for preparing a hollow fiber asymmetric composite membrane, which removes n-hexane and methanol from the hollow fiber membrane, cross-links it with a chemical cross-linking agent, then dries it in air and performs a high-temperature annealing treatment, and finally coats it with silicone rubber to seal the gaps. The temperature of the high-temperature annealing heat treatment is controlled within the range of -30°C to +40°C of the glass transition temperature of the selected layer polymer. The glass transition temperature of the preferred layer polymer is within the range of -10°C to +20°C. Compared with the existing organic-inorganic blended ultra-thin film preparation technology, it has the following advantages: the process is simpler, and thus the manufacturing cost is low; the material selection is more flexible, and thus the characteristics of different materials can be fully utilized; compared with the same type of membranes, the separation performance and mechanical properties are superior CN105339078A discloses a method for preparing a polyimide membrane, during the annealing of the membrane preparation process, a gas environment with an oxygen content of not more than 0.5% by volume surrounds the membrane, the gas environment is preferably an inert gas with a corresponding low oxygen content, more preferably nitrogen; and / or during the annealing, a corresponding gas flow is purged around the membrane. Under the condition that the temperature of the atmosphere surrounding the membrane and the distance from the membrane does not exceed 10 cm, preferably 2-10 cm, is from 280°C to the glass transition temperature of the polymer, the membrane is annealed, the temperature is preferably 280-370°C, more preferably 285-360°C, even more preferably in the range of 290-350°C, even more preferably 300-340°C, even more preferably 305-330°C, most preferably 310-320°C. These annealing conditions can obtain a membrane with significantly higher permeability and quite high selectivity, and therefore have a significantly higher yield.
[0007] It can be seen from the existing inventions that during the annealing treatment of the existing hollow fiber membrane, the environment needs to be kept dry or the epoxy atmosphere needs to be controlled to be non-oxidizing. However, in the preparation process of polyethersulfone / polysulfone fiber membrane, simply annealing the primary fiber membrane cannot effectively improve its mechanical properties. Annealing may also destroy the pore structure of the membrane, resulting in uneven pore distribution and uncontrollable pore size. Summary of the invention
[0008] The object of the present invention is to overcome at least one disadvantage of the prior art and to provide a high-performance hollow fiber membrane and its application.
[0009] The technical solution adopted by the present invention is: In a first aspect, the present invention provides a high-performance hollow fiber membrane, which is prepared by the following method: 1) preparing a spinning solution and preparing a polyethersulfone / polysulfone hollow fiber membrane by wet spinning; 2) The polyethersulfone / polysulfone hollow fiber membrane is post-treated at a relative humidity of 10-70% and 160-250° C. for 30 s to 5 min to obtain a high-performance hollow fiber membrane.
[0010] In some examples, the mass ratio of the components in the spinning solution is: 100 parts of solvent, 10-25 parts of polysulfone / polyethersulfone, 5-10 parts of organic macromolecular additive, and 2-5 parts of porogen.
[0011] In some examples, 0 to 5 parts of inorganic salt additives are added to the spinning solution by weight.
[0012] In some examples, the organic macromolecular additive of the spinning solution is one or more of maleic anhydride copolymer, polyvinyl pyrrolidone, and polyimide.
[0013] In some examples, the solvent is selected from at least one of dimethyl sulfoxide, N-methyl-2-pyrrolidone, N,N-dimethylformamide and N,N-dimethylacetamide.
[0014] In some examples, the porogen is selected from at least one of polyethyleneimine, polyethylene glycol, polyvinyl alcohol, and polyamine.
[0015] In some examples, the inorganic salt additive is selected from at least one of lithium chloride, zinc chloride, and calcium chloride.
[0016] In some examples, the polyethersulfone / polysulfone hollow fiber membrane is prepared by the following steps: 1) Weigh each component according to the ratio to prepare a spinning solution, stir and dissolve at 80-180°C, centrifuge and filter, and degas at 40-80°C to obtain a spinning solution; 2) The spinning solution is formed after passing through a coagulation bath, and the primary membrane of the polyethersulfone / polysulfone hollow fiber membrane is obtained through washing, stretching and drying.
[0017] In some examples, the temperature of the coagulation bath is 20-50°C.
[0018] In a second aspect, the high-performance hollow fiber membrane provided in the first aspect of the present invention is used in preparing materials for blood purification devices.
[0019] The beneficial effects of the present invention are: (1) Annealing treatment at a temperature close to Tg can improve the crystallinity of the primary hollow fiber membrane, promote pore size expansion and rearrangement, form a more uniform and ordered membrane structure, and improve the mechanical properties of the fiber membrane.
[0020] (2) Annealing treatment is performed at a temperature close to Tg to improve the surface morphology of the membrane fibers, reduce surface defects of the membrane fibers, reduce the adsorption of platelets on the fiber membrane surface, improve the coagulation effect, and enhance blood compatibility.
[0021] (3) By adjusting the relative humidity during annealing, the synergistic effect of moisture and heat is achieved, which helps to quickly release the stress generated during the phase change process. Hot steam can easily penetrate the pores of the membrane and process the inside of the fiber to improve the mechanical strength. At the same time, it helps the polymer chains to reach the position of minimum Gibbs free energy through rearrangement, which helps to smooth the inner and outer surfaces of the membrane and the pore surface, further reducing the adsorption of platelets on the fiber membrane surface, improving the coagulation effect, and improving blood compatibility. DETAILED DESCRIPTION
[0022] The following disclosure provides many different embodiments or examples for implementing different solutions of the present invention.
[0023] Example 1 Spinning solution formula: Polyethersulfone 20 parts 8 parts of polyvinyl pyrrolidone 3 parts of water-soluble porogen (polyethyleneimine) Solvent DMF 100 parts The specific preparation method of the hollow fiber membrane is as follows: 1) According to the above mass ratio, the required raw materials are weighed respectively, stirred and dissolved at a temperature of 100°C to form a transparent solution, centrifuged and filtered, and allowed to stand at 80°C for 4 hours to degas to obtain a spinning solution; 2) The spinning solution of step 1 is extruded from a spinneret at an extrusion speed of 3-15 ml / min by a spinning device, passed through an air bath of 5-50 cm in the air, and then placed in a coagulation bath at 20-50° C. for solidification and forming, and wound at a speed of 5-50 m / min. The formed fiber filaments are immersed in water to remove residual solvent and unreacted raw materials, and dried to obtain a primary hollow fiber membrane; 3) The primary fiber membrane was post-treated at a relative humidity of 30% and an ambient temperature of 180°C for 3 minutes to obtain a high-performance hollow fiber membrane.
[0024] Example 2 Spinning solution formula: 25 parts of polyethersulfone Maleic anhydride copolymer 10 parts Water-soluble pore-forming agent (polyethylene glycol) 5 parts Solvent DMF 100 parts The specific preparation method of the hollow fiber membrane is as follows: 1) According to the above mass ratio, the required raw materials are weighed respectively, stirred and dissolved at a temperature of 100°C to form a transparent solution, centrifuged and filtered, and allowed to stand at 80°C for 4 hours to degas to obtain a spinning solution; 2) The spinning solution of step 1 is extruded from a spinneret at an extrusion speed of 3-15 ml / min by a spinning device, passed through an air bath of 5-50 cm in the air, and then placed in a coagulation bath at 20-50° C. for solidification and forming, and wound at a speed of 5-50 m / min. The formed fiber filaments are immersed in water to remove residual solvent and unreacted raw materials, and dried to obtain a primary hollow fiber membrane; 3) The primary fiber membrane was post-treated at a relative humidity of 70% and an ambient temperature of 250°C for 30 seconds to obtain a high-performance hollow fiber membrane.
[0025] Example 3 Spinning solution formula: Polyethersulfone 10 parts Polyimide 5 parts Water-soluble porogen (polyvinyl alcohol) 2 parts Solvent DMF 100 parts The specific preparation method of the hollow fiber membrane is as follows: 1) According to the above mass ratio, the required raw materials are weighed respectively, stirred and dissolved at a temperature of 100°C to form a transparent solution, centrifuged and filtered, and allowed to stand at 80°C for 4 hours to degas to obtain a spinning solution; 2) The spinning solution of step 1 is extruded from a spinneret at an extrusion speed of 3-15 ml / min by a spinning device, passed through an air bath of 5-50 cm in the air, and then placed in a coagulation bath at 20-50° C. for solidification and forming, and wound at a speed of 5-50 m / min. The formed fiber filaments are immersed in water to remove residual solvent and unreacted raw materials, and dried to obtain a primary hollow fiber membrane; 3) The primary fiber membrane was post-treated at a relative humidity of 10% and an ambient temperature of 160° C. for 5 minutes to obtain a high-performance hollow fiber membrane.
[0026] Example 4 Spinning solution formula: Polyethersulfone 20 parts 8 parts of polyvinyl pyrrolidone 3 parts of water-soluble porogen (polyethyleneimine) 3 parts of inorganic salt additive (lithium chloride: zinc chloride: calcium chloride mass ratio = 1:1:1) Solvent DMF 100 parts The preparation process is the same as that of Example 1.
[0027] Comparative Example Spinning solution formula: Polyethersulfone 20 parts 8 parts of polyvinyl pyrrolidone 3 parts of water-soluble porogen (polyethyleneimine) Solvent DMF 100 parts The preparation methods of the hollow fiber membranes of the comparative examples are as follows: 1) According to the above mass ratio, the required raw materials are weighed respectively, stirred and dissolved at a temperature of 100°C to form a transparent solution, centrifuged and filtered, and allowed to stand at 80°C for 4 hours to degas to obtain a spinning solution; 2) The spinning solution described in step 1 is extruded from a spinneret at an extrusion speed of 3-15 ml / min by a spinning device, passed through an air bath of 5-50 cm in air, and then placed in a coagulation bath at 20-50° C. for solidification and forming, and wound at a speed of 5-50 m / min. The formed fiber filaments are immersed in water to remove residual solvent and unreacted raw materials, and dried to obtain a primary hollow fiber membrane; 3) Post-processing was performed using the post-processing process parameters described in Table 1.
[0028] Table 1. Post-processing process parameters of different comparative examples
[0029] Performance Test: The specific performance tests of each embodiment and comparative example are shown in Table 2. The test methods of different performances are as follows: 1) Water contact angle test: The fiber membranes obtained in the embodiment and the comparative example were respectively taken, dried at 105° C. for 4 hours to remove moisture, ground, and prepared into sheet samples with a diameter of 13 mm and a thickness of 1 mm using an oil pressure tablet press, and then the contact angle test was performed; 2) Pure water flux test: Refer to the pure water permeability part of GB / T 32360-2015; 3) Activated partial thromboplastin time (APTT) test: refer to YY / T0659-2017; 4) Platelet count: blood cell analyzer method; 5) β2 microglobulin clearance rate: refer to the supplementary test method of YY0053-2016; 6) Tensile performance test: Different from other polymer porous membrane materials, hollow fiber membranes require unique mechanical evaluation methods due to their hollowness, but there is currently no mature test method for their mechanical properties; this study adopted the tensile method, referring to ISO2062-1993 and GB / T3916-1997, using an electronic universal testing stretching machine, and according to the working principle of constant elongation stretching, the hollow fiber membrane with a length of 50 mm was uniformly stretched at a stretching rate of 50 mm / min until it broke, and the breaking strength and breaking elongation were recorded.
[0030] Table 2. Performance test results of hollow fiber membranes prepared in different examples
[0031] It can be found from the performance test data of Example 1 and different comparative examples in Table 2 that different post-treatment temperatures, humidity and treatment time have different effects on the mechanical strength, surface structure and pore size of the hollow fiber membrane obtained by stretching. Annealing at a temperature close to Tg can improve the crystallinity of the primary membrane of the hollow fiber membrane, promote pore expansion and rearrangement, form a more uniform and orderly membrane structure, improve the mechanical properties of the fiber membrane, and at the same time improve the surface morphology of the membrane filament, reduce the surface defects of the membrane filament, reduce the adsorption of platelets on the surface of the fiber membrane, improve the coagulation effect, and improve blood compatibility. By adjusting the relative humidity during annealing, the wet heat synergy is achieved, which helps to quickly release the stress generated during the phase change process; at the same time, hot steam is convenient for completely invading the pores of the membrane, helping the polymer chain to reach the position of the minimum Gibbs free energy through rearrangement, which helps to make the inner and outer surfaces of the membrane and the pore surface smooth, further reducing the adsorption of platelets on the surface of the fiber membrane, improving the coagulation effect, and improving blood compatibility.
[0032] (1) The post-treatment temperature needs to be within the range of 160-250°C of the glass transition temperature Tg of polyethersulfone. If the temperature is too low (Comparative Example 1), the fiber membrane cannot be effectively recrystallized and the structure cannot be rearranged, and the breaking strength and β2 microglobulin clearance rate cannot reach a high level. If the temperature is too high (Comparative Example 2), it will have an adverse effect on the toughness of the fiber membrane, and its breaking strength and breaking elongation will both decrease.
[0033] (2) Relative humidity needs to be controlled between 10% and 70%. Humidity can synergistically affect the smoothness of the fiber surface with high temperature. When the humidity is too high (Comparative Example 4), the fiber phase transition process is slow and the fracture strength of the fiber membrane is not significantly improved. When the humidity is too low (Comparative Example 3), the fiber pore surface cannot achieve the ideal smooth effect, and the adsorption of platelets is relatively high. When the fiber membrane is treated in a completely dry environment (Comparative Example 7), its fracture strength is lower and the platelet adsorption rate is higher.
[0034] (3) The post-treatment time is selected to be 30s-5min. If the treatment time is too long (Comparative Example 5), the fiber membrane will collapse during crystal rearrangement, and the originally formed large-pore structure will collapse. Although the breaking strength is improved, the clearance rate of β2 microglobulin is significantly reduced. If the treatment time is too short (Comparative Example 6), the fiber membrane structure will not have time to rearrange, and the strength cannot reach the ideal effect.
[0035] (4) The fiber membrane was not post-treated at all (Comparative Example 8). Its mechanical properties, blood compatibility, and clearance rate of the middle molecular toxin β2 microglobulin were all poor.
[0036] The hollow fiber membranes of some examples were further selected for further testing. Table 3 shows the performance test data of the hollow fiber membranes prepared under different post-treatment conditions.
[0037] Table 3. Performance comparison of hollow fiber membranes in different examples
[0038] It can be seen from Table 3 that through the design of the fiber membrane spinning formula and the adjustment of the post-processing parameters, the fiber membrane still maintains a high mechanical strength when the pore size increases, and the hydrophilicity, anticoagulant performance, β2 microglobulin clearance rate and breaking strength parameters of the obtained hollow fiber membrane can meet the use requirements.
[0039] The above is a further detailed description of the present invention, which should not be regarded as a limitation on the specific implementation of the present invention. For ordinary technicians in the technical field to which the present invention belongs, simple deduction or replacement without departing from the concept of the present invention is within the protection scope of the present invention.
Claims
1. A high performance hollow fiber membrane, characterized in that: Prepared by the following method: 1) preparing a spinning solution and preparing a polyethersulfone / polysulfone hollow fiber membrane by wet spinning; 2) The polyethersulfone / polysulfone hollow fiber membrane is post-treated at a relative humidity of 10-70% and 160-250° C. for 30 s to 5 min to obtain a high-performance hollow fiber membrane.
2. The high performance hollow fiber membrane according to claim 1, characterized in that: The mass ratio of the components in the spinning solution is: 100 parts of solvent, 10-25 parts of polysulfone / polyethersulfone, 5-10 parts of organic macromolecular additive, and 2-5 parts of porogen.
3. The high performance hollow fiber membrane according to claim 1 or 2, characterized in that: Calculated by weight, 0 to 5 parts of inorganic salt additives are also added to the spinning solution.
4. The high performance hollow fiber membrane according to claim 2, characterized in that: The organic macromolecular additive of the spinning solution is one or more of maleic anhydride copolymer, polyvinyl pyrrolidone and polyimide.
5. The high performance hollow fiber membrane according to claim 2, characterized in that: The solvent is selected from at least one of dimethyl sulfoxide, N-methyl-2-pyrrolidone, N,N-dimethylformamide and N,N-dimethylacetamide.
6. The high performance hollow fiber membrane according to claim 2, characterized in that: The porogen is selected from at least one of polyethyleneimine, polyethylene glycol, polyvinyl alcohol and polyamine.
7. The high performance hollow fiber membrane according to claim 3, characterized in that: The inorganic salt additive is selected from at least one of lithium chloride, zinc chloride and calcium chloride.
8. The high performance hollow fiber membrane according to claims 2 to 7, characterized in that: The polyethersulfone / polysulfone hollow fiber membrane primary membrane is prepared by the following steps: 1) Weigh each component according to the ratio to prepare a spinning solution, stir and dissolve at 80-180°C, centrifuge and filter, and degas at 40-80°C to obtain a spinning solution; 2) The spinning solution is formed after passing through a coagulation bath, and the primary membrane of the polyethersulfone / polysulfone hollow fiber membrane is obtained through washing, stretching and drying.
9. The high performance hollow fiber membrane according to claim 8, characterized in that: The temperature of the coagulation bath is 20-50°C.
10. Use of the high-performance hollow fiber membrane according to any one of claims 1 to 9 in the preparation of materials for blood purification devices.
Citation Information
Patent Citations
Method for preparing hollow fiber composite membrane
CN102228803A
Method for producing polyimide membranes
CN105339078A
High-performance polyimide hollow fiber membrane and preparation method and application thereof
CN110404423A